The correlation between vitamin D and the occurrence of peripheral neuropathy induced by paclitaxel chemotherapy - Zhang, Jialei; Zhang, Xiaoling; Wu, Jie (Frontiers in Medicine, 2024)
Introduction Paclitaxel, a widely used chemotherapeutic agent for various cancers, induces peripheral neuropathy (PIPN) in approximately 80% of patients, severely affecting their quality of life. The role of vitamin D in pain perception has gained attention, but its correlation with PIPN remains unclear. Methods This study included 129 cancer patients who received adjuvant paclitaxel chemotherapy from January to June 2023. Neuropathic pain was assessed using the Douleur Neuropathique 4 Questions (DN4) questionnaire, and serum levels of vitamin D and glutathione (GSH) were measured to explore the correlation between vitamin D levels and neuropathic pain induced by paclitaxel chemotherapy. Results The results showed a negative correlation between vitamin D deficiency and the occurrence of neuropathic pain (Spearman correlation coefficient of −0.324, P < 0.001). The receiver operating characteristic (ROC) curve analysis revealed that the area under the vitamin D curve for neuropathic pain was 0.681. Furthermore, after paclitaxel chemotherapy, there was a significant decrease in GSH levels in the serum of patients, with a more pronounced decline in the vitamin D-deficient group. Discussion The findings of this study indicate that higher levels of vitamin D are negatively associated with the occurrence of paclitaxel-induced neuropathic pain, suggesting that vitamin D might protect against oxidative stress. This discovery is significant for clinical treatment as it may help physicians better understand the mechanisms of pain during paclitaxel therapy and provide new strategies for the prevention and treatment of such pain. It also suggests that modulating vitamin D levels could reduce the neurotoxicity of paclitaxel, thereby improving patients’ quality of life and treatment compliance.